2005
DOI: 10.1189/jlb.0105042
|View full text |Cite
|
Sign up to set email alerts
|

Highly glycosylated α1-acid glycoprotein is synthesized in myelocytes, stored in secondary granules, and released by activated neutrophils

Abstract: Alpha-1-acid glycoprotein (AGP) is an acute-phase protein produced by hepatocytes and secreted into plasma in response to infection/injury. We recently assessed the transcriptional program of terminal granulocytic differentiation by microarray analysis of bone marrow (BM) populations highly enriched in promyelocytes, myelocytes/metamyelocytes (MYs), and BM neutrophils. These analyses demonstrated a transient, high mRNA expression of genuine secondary/tertiary granule proteins and AGP in MYs. In agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 44 publications
6
46
0
6
Order By: Relevance
“…Further analysis of the association with other measured factors after controlling for behavioral risk demonstrates a strong association with the presence of leukocytes, as well as erythrocytes. Since Lf is a product of leukocytes, this association is expected and consistent with the high level of vaginal leukocytes we have observed in high-risk women, both with and without a specific diagnosis of vaginosis or vaginitis (16,26). However, there was also an association of Lf with bacterial vaginosis, which was independent of vaginal leukocytosis, unlike Trichomonas infection.…”
Section: Discussionsupporting
confidence: 61%
“…Further analysis of the association with other measured factors after controlling for behavioral risk demonstrates a strong association with the presence of leukocytes, as well as erythrocytes. Since Lf is a product of leukocytes, this association is expected and consistent with the high level of vaginal leukocytes we have observed in high-risk women, both with and without a specific diagnosis of vaginosis or vaginitis (16,26). However, there was also an association of Lf with bacterial vaginosis, which was independent of vaginal leukocytosis, unlike Trichomonas infection.…”
Section: Discussionsupporting
confidence: 61%
“…Response to cell damage triggers systemic acute phase reaction which characterized by increasing of plasma protein synthesis in the liver. If injection of benzo(a)pyrene in subcutaneous continuously (5 times) cause cellular damage, it can be presumed that 41 kDa protein was detected in this study are the same proteins as reported by Theilgaard et al [19]. Protein 41 kDa expressed in group which injected benzo(a)pyrene (groups II, III, IV, V and VI).…”
Section: Analysis Of Plasma Protein Profile Of Mice After B Treated supporting
confidence: 86%
“…Barriers of polymerization protein were presumed to interfere cell proliferation. Theilgaard et al reported that 41 kDa protein (α1-acid glycoprotein) is one of acute phase proteins which produced by hepatocytes cells and secreted into the plasma in response to infection or cell damage [19]. Generally, cell damage is caused by radiation, toxic chemicals, drugs, toxic bacteria, physical damage, etc.…”
Section: Analysis Of Plasma Protein Profile Of Mice After B Treated mentioning
confidence: 99%
“…From a clinical perspective, alpha-1 acid glycoprotein (AGP) acts as a minor APP in humans and domestic animals, since its concentration is increased up to 3-5 fold during inflammation [16,27]. AGP is mainly produced by hepatic cells: extra-hepatic expression has even been reported in other tissues, such as in white blood cells, including cultured human monocytes [25,31], and in resting or activated polymorphonuclear leukocytes, all able to develop an immunological barrier providing a rapid defence against additional damage caused by inflammation [6,27,28,38]. While being one of the most important binding proteins in plasma [17], AGP also features several immunomodulatory functions [16], such as, for example, the stimulation of human monocytes to release pro-and anti-inflammatory cytokines [36], the inhibition of the chemotactic response of human neutrophils challenged with formyl-methionyl-leucyl-phenylalanine (fMLP) [19,41] and the reduction of platelet aggregation [35].…”
Section: Introductionmentioning
confidence: 99%